1992
DOI: 10.1080/00071669208417553
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive determination of heart rate in newly hatched chicks

Abstract: 1. Using a flexible piezoelectric probe, we detected non-invasively the cardiogenic precordial movements of domestic fowl chicks and measured heart rate (HR) daily over the first week after hatching (day 0) for comparison with previously measured embryonic HR. 2. HR of the hatchlings was much more variable than embryonic HR. The mean HR at a given age also varied among the 5 chicks measured. 3. The overall mean HR was 280 +/- 20 (SD, n = 5) bpm on day 0. This value was similar to the prepipping HR and lower th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…3, 4). This is exactly the opposite of the pattern observed in birds (Tazawa et al 1991b(Tazawa et al , 1992, but is similar to that of the direct developing frog, Eleutherodactylus coqui (Burggren et al 1990). The pattern differences likely reflect the differences between species in the magnitude of the post-hatching O2 consumption increase and the change in 02 transport efficiency resulting from the gas exchanger being in parallel (chorioallantoic membrane) with the tissues being in series (lung).…”
Section: Heart Ratesupporting
confidence: 53%
“…3, 4). This is exactly the opposite of the pattern observed in birds (Tazawa et al 1991b(Tazawa et al , 1992, but is similar to that of the direct developing frog, Eleutherodactylus coqui (Burggren et al 1990). The pattern differences likely reflect the differences between species in the magnitude of the post-hatching O2 consumption increase and the change in 02 transport efficiency resulting from the gas exchanger being in parallel (chorioallantoic membrane) with the tissues being in series (lung).…”
Section: Heart Ratesupporting
confidence: 53%
“…This pattern is observed in mammals including humans (Davignon et al, 1979). In normal (White Leghorn) chickens the increase in HR begins shortly after hatching, peaks at approximately 2 to 4 weeks of age, plateaus and slowly declines until maturity (Ringer et al, 1957;Flick, 1967;Tazawa et al, 1992). The progressive increase in HR with age is likely to be the most important means whereby CO is increased to meet the metabolic demands of rapid growth.…”
Section: Introductionmentioning
confidence: 85%
“…These results were in agreement with those of Druyan et al [166], who found that generation S3 chicks from their AS-S line had a significantly higher heart rate on day of hatch than that of generation S3 chicks from the AS-R line. It was reported [167] that heart rate began to increase shortly after hatch, and reached a peak close to 4 wk of age; thereafter, it declined slowly [168]. The AS-S selected line exhibited increased heart rate only between d 1 and d 7, with a decline thereafter toward d 17, while the birds were kept under standard brooding condition [57].…”
Section: The Heartmentioning
confidence: 99%